Strategi Pemasaran dalam Meningkatkan Penjualan pada Toko Sepeda Mega Jaya Tambun Selatan - Michael Aris Willson; Hadita Hadita (Universitas 45 Surabaya, 2023)
This research aims to implement marketing strategies to increase sales of the Megajaya Bicycle Shop. The obstacles faced by the Mega Jaya Bicycle Shop in implementing its marketing strategy and efforts to overcome the obstacles faced by the Mega Jaya Bicycle Shop in implementing its marketing strategy. This research uses a qualitative descriptive method using observation and interview data collection techniques. Based on the researcher's findings regarding marketing strategies to increase sales of the Megajaya Bicycle Shop, the researchers concluded that:: As a bicycle shop, this strategy is not optimal and sales have not increased. (2) Implementing a marketing strategy that is right on target will help the Mega Jaya Bicycle Shop increase its sales. As bicycle shop, this strategy is not optimal and sales do not increase. (3) Implementation of a positioning marketing strategy will contribute to increasing sales of the Mega Jaya Bicycle Shop. By implementing this strategy, the Mega Jaya Bicycle Shop is believed to be able to increase its sales. (4) The impact of the marketing strategy of segmentation, targeting and positioning implemented by the Mega Jaya Bicycle Shop is still less than optimal. In the end, the market segmentation is not broad enough, especially if the sales focus is only in the area South Bekasi Tambun Regency and surrounding areas. Furthermore, implementing this strategy has difficulty increasing sales because the target market is less developed.